Power calculations and placebo effect for future clinical trials in progressive supranuclear palsy. Issue 5 (7th March 2016) - Stamelou, Maria; Schöpe, Jakob; Wagenpfeil, Stefan; Del Ser, Teodoro; Bang, Jee; Lobach, Iryna Y.; Luong, Phi; Respondek, Gesine; Oertel, Wolfgang H.; Boxer, AdamL.; Höglinger, Günter U.; ,
ABSTRACT: Background: Two recent randomized, placebo‐controlled trials of putative disease‐modifying agents (davunetide, tideglusib) in progressive supranuclear palsy (PSP) failed to show efficacy, but generated data relevant for future trials. Methods: We provide sample size calculations based on data collected in 187 PSP patients assigned to placebo in these trials. A placebo effect was calculated. Results: The total PSP‐Rating Scale required the least number of patients per group (N = 51) to detect a 50% change in the 1‐year progression and 39 when including patients with ≤ 5 years disease duration. The Schwab and England Activities of Daily Living required 70 patients per group and was highly correlated with the PSP‐Rating Scale. A placebo effect was not detected in these scales. Conclusions: We propose the 1‐year PSP‐Rating Scale score change as the single primary readout in clinical neuroprotective or disease‐modifying trials. The Schwab and England Activities of Daily Living could be used as a secondary outcome. © 2016 International Parkinson and Movement Disorder Society